(untitled) (JURNAL KEPERAWATAN, 2014)
Abstrack: Introduction Post-traumatic stress disorder is a stressful experience that occurred as a result of disasters that may occur in every individual and children are vulnerable to get PTSD. Purpose of this study was to know charactheristics of age, gender and educationas well the different post-traumatic stress disorder in childrens in watershed tondano after flash flood in Manado. The design of this study using descriptive research design using a study group. Samples are 94 people. The data was collected by using questionnaire then the data were processed and analyzed by independent t-test with a significance level (α) of 0.05. based on the test results of the analysis using independent t-test P = 0.041 obtained value <α = 0.05, it can be concluded that there are differences in post-traumatic stress disorder in children after the Tondano watershed flood the city of Manado. Concluded that there are differences of post-traumatic stress disorder in childrens in watershed tondano after flash flood in Manado. Keywords : Post Traumatic Stress Disorder, Children. Abstrak: Pendahuluan Post-traumatic stress disorder adalah pengalaman stres yang terjadi akibat bencana yang dapat terjadi pada setiap individu dan anak–anak merupakan kelompok yang rentan mendapatkan PTSD. Tujuan penelitian diketahui karakteristik umur, jenis kelamin,dan pendidikan serta adanya perbedaan pada anak di daerah aliran sungai tondano pasca banjir bandang kota Manado. Desain penelitian desain penelitian deskriptif dengan menggunakan kelompok studi. Sampel 94 responden. Pengumpulan data menggunakan kuisioner selanjutnya data diolah untuk dianalisa dengan uji independent t-test dengan tingkat kemaknaan (α) 0,05. Hasil penelitian berdasarkan hasil analisis menggunakan uji independent t-test diperoleh nilai P = 0,041 < α = 0,05, maka dapat disimpulkan bahwa ada perbedaan post traumatic stress disorder pada anak di daerah aliran sungai tondano pasca banjir bandang kota Manado. Kesimpulan dalam penelitian ini ada perbedaan post-traumatic stress disorder pada anak di daerah aliran sungai tondano pasca banjir bandang kota Manado. Saran untuk pemerintah dan LSM dapat membantu penanganan PTSD sehingga kejadian traumatik ini dapat diatasi. Kata kunci : Post Traumatic Stress Disorder, Anak.